Healing Spaces Designing Physical Environments to Optimize Health, Wellbeing and Performance - Sternberg, Esther M.; Engineer, Altaf; Ida, Aletheia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The field of design and health, formerly known as the domain of healthcare design professionals, has now reached a turning point with the proliferation of a plethora of non-invasive wearable technologies, to provide the objective and near-real-time measurement of the impact of many features of the built environment on aspects of health, wellbeing and performance. In turn, new materials and the Internet of Things are allowing the development of smart buildings, which can interact with occupants to optimize their health, wellbeing, performance and overall experience. Companies that have previously focused on positioning themselves as "green" are now turning to positioning themselves in the marketplace as both green and healthy. This Special Issue will include articles that address new cutting edge technologies and materials at the interface between design and health, and review some of the latest findings related to studies which use these technologies. This SI will also suggest exciting future directions for the field. It will include articles which focus on the objective data gathered to document the effects of the built environment on health. Importantly, it will focus on the use of innovative methods of measurement, such as state-of-the-art wearable and environmental sensors, quantifying some aspects of health, such as stress and relaxation responses, activity, posture, sleep quality, cognitive performance and wellbeing outcomes. It will also examine the impacts of different elements of the built environment on these health and wellbeing outcomes. The published articles will focus on the design interventions informed by these measurements, along with innovative integrated building materials that can shape the design of built environments for better health, productivity, and performance. It will also address the return on investment (ROI) of such design interventions. This Special Issue will provide both the foundational knowledge and fundamentals for characterizing human health and wellbeing in the built environment, as well as the emerging trends and design methods for innovations in this field.